Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Monitoring, Evaluation and Learning approaches in an adaptive management context - Tsui, Josephine (EPS PEAKS, ODI, 2016)

Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change

Building Bridges to an Uncertain Future Lived Now: Lessons from the Use of Participatory Action Research and Theory of Change Towards A Realistic Community-Based Participatory Monitoring and Evaluation System - Avila, Enrique M.; Tolentino, Lutgarda L.; Binondo, Claudia B.; Perez, Maripaz L.; Apgar, J. Marina (International Journal of Agriculture System, 2016)
Building on experience from the CGIAR Research Program on Aquatic Agricultural Systems implemented by WorldFish in the Visayas and Mindanao regions of the Philippines, known as the VisMin Hub, we describe the development and evolution of a monitoring and evaluation (M&E) system emerging from the facilitated action-reflection cycles of testing and adopting theories of change carried out with community partners through participatory action research (PAR). The former guides our community partners and us, as members of the potentially emergent PAR groups, towards the realization of the community’s vision; the latter facilitates learning to understand what, how and why change is unfolding. Unlike the conventional M&E system where indicators are pre-set at the beginning of program implementation, these processes result in an organically-evolved, communitybased participatory M&E system that is continuously revised according to contexts to guide communities towards realizing their visions. Its ultimate outcome is enhanced people’s capacity to own the product and process, giving rise to an internally-driven change. Towards the end, the paper offers an iterative discussion of learnings from implementing such an approach.
Keywords: Aquatic agricultural systems; CGIAR; Community-based participatory MEL; Learning; Participatory action research; research in development; theory of change